Grammarian Pioneers Opinion about Citation of Hadith - ALGUNIDEL, SAUD ABDULAZIZ (Arab Journal for Sciences and Research Publishing, 2019)
This research light on the question of citing the Prophet’s Hadith. There have been many sources of grammar and Arabic language، including the Holy Quran، the Prophet’s speech and poetry and prose، and this research will discuss the different views that authorized and prevented the question of the martyrdom of the Prophet، whether they are applicants or contemporary. This research was divided into a preface and an introduction that included the importance and objectives of the research and its problems and dealt with a number of previous studies that clarified this issue. The research also included three main topics. The first topic discussed the prevention of quoting the Prophet’s Hadith and their evidence and response. From the opinion of the health of the martyrdom of the speech، and evidence and respond to them، while the third topic dealt with the opinion of the Mediterranean position، and the conclusion.